2015
DOI: 10.1103/physrevc.92.035810
|View full text |Cite
|
Sign up to set email alerts
|

Thermal evolution of hybrid stars within the framework of a nonlocal Nambu–Jona-Lasinio model

Abstract: We study the thermal evolution of neutron stars containing deconfined quark matter in their core. Such objects are generally referred to as quark-hybrid stars. The confined hadronic matter in their core is described in the framework of non-linear relativistic nuclear field theory. For the quark phase we use a non-local extension of the SU(3) Nambu Jona-Lasinio model with vector interactions. The Gibbs condition is used to model phase equilibrium between confined hadronic matter and deconfined quark matter. Our… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 70 publications
1
17
0
Order By: Relevance
“…It has been shown that vector interaction contributions in the description of quark matter plays a crucial role in the description of massive hybrid stars in agreement with observational data [25,59,76,92,[133][134][135][136][137][138]. These contributions have been investigated for different quark models [135,137,138]), and applied to neutron stars studies [59,76,[134][135][136].…”
Section: B Quark Phasementioning
confidence: 91%
“…It has been shown that vector interaction contributions in the description of quark matter plays a crucial role in the description of massive hybrid stars in agreement with observational data [25,59,76,92,[133][134][135][136][137][138]. These contributions have been investigated for different quark models [135,137,138]), and applied to neutron stars studies [59,76,[134][135][136].…”
Section: B Quark Phasementioning
confidence: 91%
“…The first aspect of our strategy is to use a conservative model of cooling which is not contaminated by the uncertainties in the rates of rapid neutrino emission processes, which in turn strongly depend on the composition of dense matter at densities above the saturation of nuclear matter. Modern simulations of cooling of neutron stars (see, for example, the work by different groups on hadronic models [38][39][40][41][42][43] and hybrid star models [44][45][46][47]) demonstrate that fast neutrino processes do not operate in low-mass neutron stars with M ≤ 1.5M ⊙ because each such process is associated with a certain density threshold (which need not be sharp, see in particular Refs. [40,41] for this type of modeling).…”
Section: Introductionmentioning
confidence: 99%
“…For that purpose we consider the thermal evolution of these objects, by making use of state of the art cooling calculations [62][63][64]. We employ the most recent thermal emission and cooling mechanisms available, that have also been used to explain the thermal properties of the cooling neutron star in Cassiopeia A [62,[65][66][67].…”
Section: Evolution Aspectsmentioning
confidence: 99%